Simple vs ugly adnexal lesions: is ultrasonography alone good enough? - Chauhan, Rahul Dev; Mathur, Yashvir (International Journal of Research in Medical Sciences, 2019)
Background: Ultrasound (USG) is easily available and effective imaging modality for adnexal lesions. A simple looking lesion on ultrasound is usually benign and an ugly looking adnexal lesion is either benign or malignant. This study aims to evaluate the varied appearance of simple and ugly benign adnexal lesions on USG and to find out any additional role of colour Doppler in such suspected benign lesions. The confirmation of diagnosis was done either by follow up appearance of lesions on USG or by histopathological evaluation. Methods: A total of 55 consecutive female patients with age between 18 to 50 years were enrolled in this prospective cross sectional study. USG and colour Doppler for all the lesions were done. The patients found to have malignant lesions on histopathological examination, were later excluded from the analysis. Follow up USG was done for all the cases. Those cases wherein there was no resolution of lesions even after 08 weeks, were given an option to undergo laparoscopy as next management step. Results: Out of 50 benign adnexal masses, 88% masses were ovarian in origin and 12% were tubal masses. Ovarian masses included hemorrhagic cysts, endometriosis, simple cysts, serous cystadenomas and ovarian dermoid. All extra-ovarian masses were hydrosalpinx. Colour Doppler did not add any additional finding. Some of the patients underwent diagnostic laparoscopy followed by excision of masses in majority of them. Conclusions: Benign adnexal lesions can have varied appearance ranging from simple to ugly on USG. Ultrasonographic features of benign lesions on USG can be appreciated very well even without further use of colour Doppler or cross sectional imaging. Follow up USG remains key modality for benign adnexal masses in absence of MRI.